Social Media Engagement and Stock Return of Companies Included in Kompas100 (Case of Youtube and Twitter) - Santosa, Jason Gamaliel; Nainggolan, Yunieta Anny (Journal of Business and Management, 2020)
Abstract. Communication media used by human change over time. Nowadays, most activities in communication occur in online social media. In social media, users can share contents publicly in the form of text, photos, and videos. It could create engagement between the content creator and social media users. Companies’ decision to use social media as a platform to share information to public must be considered carefully. Because the content shared might include vital and important information about the company, such as marketing plan and projected future growth of the company. So, this research has an objective to know whether social media engagement affects stock return of companies listed in Kompas100. Data collected secondary by accessing publicly available sources. This research uses Multiple Linear Regression through SPSS programme. The results show that social  media engagement has a very small negative impact on geometric mean stock return and no impact to arithmetic mean stock return. It might have happened because the content shared by the companies neither included vital nor important information hence the social media engagement did not affect stock return. The results of this research are expected to be considered for companies to utilize social media and create engagement with the users.Keywords: Social Media, Social Media Engagement, Kompas100, Stock Return